Molecular Detection of Feline Herpesvirus 1 in Cats in Mosul City - Waleedismailkhudhur; S.Y.Albaroodi; Bashar sadiqnomi (The Indian Veterinary Journal, 2025)
The study included 200 cats of various ages, genders, nature of breeding, source, and vaccination programs, as well as health status. They were examined clinically, and the clinical signs appearing on them were recorded, and then swabs from the conjunctiva of the eyes, the oropharyngeal, and the nose were collected and  transferred  to the laboratory.The feline herpes virus's DNA molecule was examined using swabs obtained for the investigation. The DNA was extracted, and a specific primer was then used in the polymerase chain reaction technique to identify the thymidine kinase template gene.. The extract DNA for each sample an final reaction volume of 182 bp. After recording positive samples in many samples, 10 positive samples were positive and their DNA was purified. Then the genetic sequence of each sample was performed in the Marcogen laboratory, Korea, and then the similarity to the genetic sequence in the database was determined using the Basic Local Alignment Search program, which is located on the electronic page. For the National Center for Life Technologies (NCBI) (www.ncbi.nlm.nih.gor), the multiple sequence alignment was then created using the Cluster Omega program, and then the phylogenetic tree was created using the MEGA 7 program.